(untitled) (Vietnam Journal of Community Medicine, 2022)
Introduction and objectives: Varicocele is among the most common causes of male infertility. Our study aimed to evaluate the effectiveness of microsurgical varicocelectomy in treating male infertility. Subjects and methods: Data were collected prospectively from 55 cases of infertile men with clinical varicocele who underwent microsurgical varicocelectomy from Dec 2018 to Dec 2021 at the Department of Urology, 19-8 Hospital, Ministry of Public Security. Patients were followed-up 3, 6 and 9 months using semen analysis and hormonal tests. Results: Mean age of patients was 29,09 ± 2,72 years. Primary infertility was found in 83,64% of patients and the prevalence of secondary infertility was 16,36%. Symptom improvement has been reported in most of patients after the surgical. The sperm analysis revealed statistically significant increases in sperm concentration, progressive sperm motility and normal morphology (p<0,05). The adjusted testosterone levels increased in hypogonadism group. Reported pregnancy rates was 54,55%, besides the rate of spontaneous pregnacy was 43,64%. Conclusions: Microsurgical varicocelectomy is an effective procedure for the treatment of varicocele, especially in patients who were infertility. This can improve semen parameters and increase spontaneous pregnacy rates.